Ethnic differences in 25-year risk of incident chronic kidney disease among people with type 2 diabetes in New Zealand. Issue 6 (15th December 2022) - Yu, Dahai; Wang, Zheng; Cai, Yamei; Osuagwu, Uchechukwu Levi; Pickering, Karen; Baker, John; Cutfield, Richard; Orr-Walker, Brandon J; Sundborn, Gerhard; Jayanatha, Kalpa; Zhao, Zhanzheng; Simmons, David
Abstract : Introduction: Insights into ethnic differences in the natural history of chronic kidney disease (CKD) among people with type 2 diabetes mellitus (T2DM) might inform clinical strategies to address disparities in hospitalization and mortality. Risks of CKD II–V stages over a 25-year period between New Zealand Europeans (NZEs), Māori and Pasifika, and with T2DM in Auckland, New Zealand (NZ) were compared. Research design and methods: As a primary care audit program in Auckland, the Diabetes Care Support Service was linked with national registration databases. People with existing CKD II–V were ruled out. To balance potential confounders, we applied a tapered matching method . 'Quasi-trial'-matched cohorts were set up separately between Māori and NZE and between Pasifika and NZE. Ethnic population differences in risk of any and each stage of CKD over 1994–2018 were examined by weighted Cox regression model. Results: The HRs for developing any CKD, CKD stages II–V for Māori (n=2215) versus NZE (n=2028) were 1.18 (95% CI 0.99 to 1.41), 1.10 (95% CI 0.91 to 1.32), 1.70 (95% CI 1.19 to 2.43), 3.93 (95% CI 2.16 to 7.14), and 3.74 (95% CI 1.74 to 8.05), respectively. Compared with NZE (n=2474), the HRs for developing any CKD, CKD stages II–V for Pasifika (n=3101) were 1.31 (95% CI 1.09 to 1.57), 1.26 (95% CI 1.05 to 1.52), 1.71 (95% CI 1.14 to 2.57), 3.75 (95% CI 1.40 to 10.05), and 4.96 (95% CI 1.56 to 15.75), respectively. Conclusions: Among people with T2DM in NZ, significant ethnic differences exist in the risk of progressing to each stage of CKD (stage V in particular). Mechanism studies underlying these differences, as well as the need for identification of biomarkers to predict the early onset renal lesion, are warranted.